PENGARUH CARA TANAM LEGOWO DAN DOSISI PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L) VARIETAS CIHERANG - Amran Jaenudin; Mastari Mastari (Agroswagati Jurnal Agronomi, 2017)
This study aims to determine how planting legowo and urea fertilizer on the growth and yield of rice (Oryza sativa L.) Ciherang. The experiments were performed in public paddy Banjarwangunan village Mundu Subdistrict Cirebon regency, West Java province in March until July 2016.The experimental design was a randomized block design (RAK), consisted of 9 treatments and each treatment was repeated 3 times. The treatment consisted of (Legowo 2: 1 and Urea 100 kg), (Legowo 2: 1 and Urea 200 kg), (Legowo 2: 1 and Urea 300 kg), (Legowo 3: 1 and Urea 100 kg) , (Legowo 3: 1 and Urea 200 kg), (Legowo 3: 1 and Urea 300 kg), (Legowo 4: 1 and Urea 100 kg) (Legowo 4: 1 and Urea 200 kg), (Legowo 4: 1 and Urea 300 kg).The results showed that planting method legowo and urea fertilizer there is no influence interaction between planting method legowo and urea fertilizer to all the variables of growth and yield. However, there is an independent effect on planting method legowo against Total Tillers per Clump (34 pieces) and Volume Root (143,3 ml) and the influence of self-weight of urea to wet paddy (GKP) / plots (9,2 kg / plot ). However, the provision of urea fertilizer at the level of 200 kg /ha give the best effect compared with the level of the others, while increasing production 13%.Results of heavy wet paddy (GKP) / plot (kg/ha), the highest in the treatment of Urea 200 kg / ha give the best independent influence on the average grain yield per plot harvested dry with average weight 9.2 kg / plot , equivalent to 8 tonnes/ha.